Pricing a package of services: When (not) to bundle - Felix Ketelaar; Dezsö Szalay (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
We study a tractable two-dimensional model of price discrimination. Consumers combine a rigid with a more flexible choice, such as choosing the location of a house and its quality or size. We show that the optimal pricing scheme involves no bundling if consumer types are affiliated. Conversely, if consumer types are negatively affiliated over some portion of types then some bundling occurs.
urn:nbn:de:bvb:19-epub-22183-5
Keywords: D42; D82; D86; 330; Price discrimination; Bundling; Monopoly; Multidimensional screening